The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1158/2326-6066.cir-15-0024
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Benefit of PD-L1 Blockade in Lung Cancer Associated with JAK3 Activation

Abstract: PD-1 immune checkpoint blockade occasionally results in durable clinical responses in advanced metastatic cancers. However, mechanism-based predictors of response to this immunotherapy remain incompletely characterized. We performed comprehensive genomic profiling on a tumor and germline sample from a patient with refractory lung adenocarcinoma who achieved marked long-term clinical benefit from anti-PD-L1 therapy. We discovered activating somatic and germline amino acid variants in JAK3 that promoted PD-L1 in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 46 publications
(51 reference statements)
1
45
0
Order By: Relevance
“…In addition, others have demonstrated that oncogenic alterations can induce PD-L1 expression. [48][49][50] The correlations we report between lymphocyte infiltration (in particular CD3 and CD8 C ) and distribution (immunotype) with PD-L1 expression, and the lack of any association with BRAF mutational status, suggest that PD-L1 expression by human melanoma cells can be explained predominantly by adaptive resistance. We only found a single case where PD-L1 expression was observed in greater than 5% of the tumor cells in the absence of any CD8 C T cells, a result consistent to Taube and colleagues' finding.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, others have demonstrated that oncogenic alterations can induce PD-L1 expression. [48][49][50] The correlations we report between lymphocyte infiltration (in particular CD3 and CD8 C ) and distribution (immunotype) with PD-L1 expression, and the lack of any association with BRAF mutational status, suggest that PD-L1 expression by human melanoma cells can be explained predominantly by adaptive resistance. We only found a single case where PD-L1 expression was observed in greater than 5% of the tumor cells in the absence of any CD8 C T cells, a result consistent to Taube and colleagues' finding.…”
Section: Discussionmentioning
confidence: 72%
“…Although currently there are not sufficient data to compare responses to immunotherapy among different ethnicities since only 1-2% of the participants in the published immunotherapy clinical trials are African Americans [59,60], our results suggest African American NSCLC patients may have an overall higher response rate due to ethnicityspecific JAK3 mutations. However, we should point out that although both p.V722I and p.P132T in JAK3 are activating mutations [39], only p.V722I JAK3 mutant protein has been shown experimentally to promote PD-L1 expression [40]. Although it is implied that the p.P132T mutant protein would also activate PD-L1 expression, it should be directly tested.…”
Section: Discussionmentioning
confidence: 98%
“…The JAK3 p.V722I germline mutation has been identified in a lung cancer patient with long-term benefit to anti-PD-L1 antibody atezolizumab [40]. Furthermore, it was shown that the mutant JAK3 protein promoted PD-L1 expression in vitro and PD-L1 positivity is substantially enriched in clinical tumor samples with JAK3 mutations [40]. Therefore, we predict the 6.7% patients in our cohort may respond to anti-PD1 therapy.…”
Section: Germline Mutations With Clinical Implicationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Notably, PTEN suppresses PI3K expression, and PTEN loss results in altered PI3Kβ expression; targeting PI3Kβ with an antibody enhanced tumor response to anti-PD-1 antibody in mouse models of melanoma with PTEN loss, suggesting the therapeutic potential of such combinations in melanoma patients with PTEN loss. A case report of one patient with metastatic lung adenocarcinoma who had an extraordinary response to anti-PD-1 antibody treatment revealed somatic and germline JAK3 mutations at the same allele [19]. Transduction of these mutants enhanced PD-L1 expression on lung cells, suggesting a mechanism for the patient's exceptional tumor response to anti-PD-1 antibody.…”
Section: Discussionmentioning
confidence: 98%